Pengaruh Disiplin Kerja, Kompensasi, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada CV Ar Royhan Tulungagung - Nur Hidayah, Sinta; Agus Buniarto, Edwin; Harianto, Kukuh (Cahaya Ilmu Bangsa, 2025)
This study aims to determine the effect of work discipline, compensation, and work environment on employee performance at CV Ar Royhan Tulungagung. The variables in this study are Work Discipline (X1), Compensation (X2), Work Environment (X3), and Employee Performance (Y). This study uses a quantitative method using data collection techniques in the form of interviews, observations, literature studies and questionnaires. While the analysis used is validity test, reliability test, classical assumption test, multiple linear regression test, t test and f test and coefficient of determination. Sampling in this study used purposive sampling by taking into account all employees of CV Ar Royhan totaling 80 people based on the results of the research conducted. The results of this study used the SPSS 25.0 program using a significance level of 5% or 0.05 with the results (1) partially work discipline has a significant effect on employee performance with a significance value of 0.000 <0.05 which means H1 is accepted and Ho1 is rejected. (2) Partially, compensation has a significant effect on employee performance with a significant value of 0.000 < 0.05, which means that H2 is accepted and Ho2 is rejected. (3) Simultaneously, work discipline, compensation, and work environment have a significant effect on employee performance with a significant value of 0.000 < 0.05, which means that Ha4 is accepted and Ho4 is rejected